2021
DOI: 10.1021/acsnano.0c10874
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Reconfigurable Nanoparticle Binary Superlattices

Abstract: The presence of diffusionless transformations during the assembly of DNA-functionalized particles (DFPs) is highly significant in designing reconfigurable materials whose structure and functional properties are tunable with controllable variables. In this paper, we first use a variety of computational models and techniques (including free energy methods) to address the nature of such transformations between face-centered cubic (FCC) and body-centered cubic (BCC) structures in a three-dimensional binary system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Ordered NP assembly (Figure 5a) by external stimuli has become a crucial strategy in designing and fabricating ordered functional materials such as superlattices, [22,94,95] crystals, [96,97] Adv. Mater [54] Copyright 2016, Wiley-VCH.…”
Section: Ordered Np Superstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordered NP assembly (Figure 5a) by external stimuli has become a crucial strategy in designing and fabricating ordered functional materials such as superlattices, [22,94,95] crystals, [96,97] Adv. Mater [54] Copyright 2016, Wiley-VCH.…”
Section: Ordered Np Superstructuresmentioning
confidence: 99%
“…Ordered NP assembly ( Figure a) by external stimuli has become a crucial strategy in designing and fabricating ordered functional materials such as superlattices, [ 22,94,95 ] crystals, [ 96,97 ] helical superstructures, [ 98 ] and honeycomb‐like superstructures. [ 99 ] Compared with disordered NP aggregation, ordered NP aggregation generally need a precise and rigorous assembly process, such as solvent evaporation‐induced assembly at air/liquid–liquid interfaces, destabilization‐based assembly by slow diffusion of the nonsolvent into solvent, and DNA‐guided NP assembly by programmable sequence.…”
Section: Nano/microscale Materials By Stimuli‐responsive Np Aggregationmentioning
confidence: 99%
“…2D). Mao et al 57 used molecular dynamics (MD) methods to study the transition of two-component DNA-modified nanoparticles between FCC and BCC crystals. They found that the structural rearrangements between the BCC and FCC structures are thermodynamically reversible and related to the crystallite size.…”
Section: Nanoparticles Modified With Different Dna Strandsmentioning
confidence: 99%
“…For example, DNA nanostructures are highly promising drug delivery vehicles because of their high biocompatibility, in vivo stability, and ability to deliver large quantities of cargo to specified targets; DNA wireframe cages can carry proteins and selectively enter cells via suitably designed receptors on the cage surface. , DNA molecules can also be employed to control the diameter and open-state lifetime of peptide pores for single-molecule analytics . The specificity offered by designing BP sequences has also been exploited for the self-assembly of “patchy” colloidal particles coated with complementary DNA strands. …”
Section: Introductionmentioning
confidence: 99%